Multimodal group-based tele-prehabilitation for cancer patients and caregivers: a pragmatic multicentre hybrid implementation-effectiveness study protocol - Doré, Isabelle; Piché, Alexia; Montiel, Corentin; Lambert, Sylvie D.; Gillis, Chelsia; Dufresne, Sébastien S.; Riesco, Eléonor; Jardel, Pauline; Pavic, Michel; Samouëlian, Vanessa; Dubé, Samuel; Brisson, Isabelle; et al. (Frontiers in Oncology, 2025)
BackgroundMultimodal prehabilitation can optimize the physical and psychological health of cancer patients, reduce treatment side effects, hospital stay, and accelerate recovery. The support provided by caregivers reduces the demands on the health care system and can be key in the uptake and maintenance of healthy lifestyle behaviours. However, caregivers support comes at a high cost to their own health. Physical activity can help caregivers maintain their health at the level required to successfully perform their vital roles. Our team has designed the first group-based multimodal tele-prehabilitation program targeting both patients and caregivers: coACTIF. This paper presents the protocol of this implementation-effectiveness study.MethodsThis pragmatic, multicentre, hybrid implementation-effectiveness study uses a pre-post-follow-up mixed methods convergent parallel design. The prehabilitation program implementation and effectiveness will be tested in three cities of various sizes in Quebec, Canada. The prehabilitation program includes a virtual supervised group-based exercise program and a web-based educational platform providing learning opportunities and resources on healthy lifestyles and self-management strategies. The study aims to recruit a convenience sample of 100 units (a unit can be a dyad, a patient alone or a caregiver alone). Study participants are French-speaking, adults, preoperative cancer patients and/or their adult caregivers. The implementation and effectiveness are assessed through indicators of the RE-AIM framework: Reach, Effectiveness, Adoption, Implementation and Maintenance. Functional fitness and health outcomes are assessed pre-post intervention and 90-day post-surgery. Interviews with patients, caregivers and health professionals will be conducted to document implementation barriers, facilitators and strategies to facilitate scaling-up of the intervention across various health organisations using the Consolidated Framework for Implementation Research (CFIR).Discussion and disseminationThis study will provide evidence from various real-world cancer care settings about the implementation and effectiveness of an innovative tele-prehabilitation intervention that aims to rapidly engage cancer patients and caregivers. This intervention has the potential to accelerate and facilitate behaviour change early in the cancer continuum with the objective of optimizing the whole cancer experience and future scaling-up across a variety of cancer care units. Our team will disseminate coACTIF results through reports to stakeholders, scientific manuscripts and presentation at clinical and scientific conferences.